Translanguaging in English Language Teaching: Perceptions of Teachers and Students - Natalia Vasilievna Chicherina; Svetlana Yurievna Strelkova (MDPI AG, 2023)
The wide spread of English as the dominant language in higher education around the world due to the processes of globalization and internationalization, opposed to the emerging trend for 'nationalism' or 'de-globalization', has recently led to new interest in the role of languages other than English in teaching and learning processes. This article investigates the beliefs and attitudes of Russian university students and teachers concerning the value of English language teaching and the language of instruction in ELT to explore their perceptions of ELT in a Russian monolingual university. The participants of this study were 581 students and teachers of two Russian universities. The research questions were approached from a quantitative perspective with the analysis of data obtained from a questionnaire. The main statistically significant findings include the following: the value of ELT, supported by English-medium instruction is high for all groups of respondents; translanguaging practices in ELT with the minimized use of Russian as the mother tongue are a top priority both for the students and the teachers; additional language learning experience makes students more committed to more intensive language studies and increases their confidence in their ability to study non-language subjects in English.